2023
DOI: 10.21123/bsj.2023.8410
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Solution of Sub diffusion Bio heat Transfer Equation

Abstract: In this paper, author’s study sub diffusion bio heat transfer model and developed explicit finite difference scheme for time fractional sub diffusion bio heat transfer equation by using caputo fabrizio fractional derivative. Also discussed conditional stability and convergence of developed scheme. Furthermore numerical solution of time fractional sub diffusion bio heat transfer equation is obtained and it is represented graphically by Python.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The proposed study utilizes a time fractional drug diffusion problem described by Equations ( 3), ( 4) and (5) to evaluate the diffusion of drug within the human dermal layer. To accomplish this, we employ a fractional-order explicit finite difference method, as developed in Equations ( 8), ( 9), (10), (11) and (12), to predict drug diffusion at specific grid points (x i ,t k ) within the discretized dermal region. The simulation employs dimensionless quantities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed study utilizes a time fractional drug diffusion problem described by Equations ( 3), ( 4) and (5) to evaluate the diffusion of drug within the human dermal layer. To accomplish this, we employ a fractional-order explicit finite difference method, as developed in Equations ( 8), ( 9), (10), (11) and (12), to predict drug diffusion at specific grid points (x i ,t k ) within the discretized dermal region. The simulation employs dimensionless quantities.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we examine the stability of the solution obtained through the application of the explicit method Equations ( 8), ( 9), ( 10), (11) and (12) to the TFDDE Equations ( 3), ( 4) and (5).…”
Section: Stability Of Numerical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, considerable attention has been directed towards the burgeoning field of "Fractional Calculus" by numerous researchers, driven by its diverse applications across various scientific and engineering domains (1)(2)(3)(4)(5) . Introducing fractional operators into classical differential equations results in complex challenges when solving resulting fractional-order partial differential equations (6) .…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that, most of the models are developed by using ordinary and partial derivatives, which means that they are free from the memory effect. In the last two decades, fractional differential equations (FDEs) have been widely used in the modeling of real life problems [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%